Technology-Supported Active Learning in a Flexible Teaching Space - Jirarat Sitthiworachart; Mike Joy; Emma King; Jane Sinclair; Jonathan Foss (MDPI AG, 2022)
Active learning is increasingly of interest within Higher Education. The use of technology provides, in theory, the opportunity for more effective active learning, but in practice the majority of learning technology usage is still for "traditional" approaches. Conventional staff training is failing to address this. The authors' university has provided an experimental technology-rich teaching space (the Teaching Grid) for supporting teachers as they experiment with the delivery of innovative, technology-based teaching. This study investigates teachers' experiences of trialling active learning approaches within the Teaching Grid using four case studies. The results suggest that the Teaching Grid can be effectively used to support teacher professional development, and the experience of using the facility encourages teachers to integrate technology into their future teaching plans. Five factors are identified which contribute to the promotion of active learning. Teachers' perceptions of their experience indicate not only the intention to use technology more but also an increased awareness of its potential and openness to adopt more active, student-focused approaches. The broader significance of this work is to identify an alternative model for teacher development which, in contrast to most current approaches, has a demonstrable positive impact on fostering innovative, technology-based pedagogy.